The Commodification of Religion in The 2012 Regional Election of Purwakarta Regency - Muhamad Ridwan Effendi (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2022)
This study aims to describe the involvement of religious instruments in the dynamics of the 2012 Regional Head Elections for the Regent and Deputy Regent of Purwakarta Regency. This study uses a qualitative method with the dramaturgical approach of Erving Goffman on symbolic interactionism and Max Weber on social action theory. This study indicates that the normative use of religious elements is used as a weapon for candidates as a political commodity to attract mass sympathy and highlight the identity of a particular group. Among the religious issues used in the Pilkada Purwakarta could be the use of religious symbols, statements, figures and places used by the contestants and political constituents in Purwakarta.